Observations upon liberal education - Turnbull, George, 1698-1748 (Natural law and enlightenment classics., 2003)
"Although Francis Hutcheson is widely considered the father of the Scottish Enlightenment, his contemporary George Turnbull (1698-1748) equally embodied in his life, and produced with his pen, the moral and intellectual forces and principles by which the Scottish Enlightenment came to be known." "Turnbull is one of the earliest and perhaps one of the least-remembered authors in the Scottish tradition. While teaching moral philosophy at Marischal College, Aberdeen, he mentored Thomas Reid, who became the founder of the important common-sense school of Scottish moral philosophy. Knud Haakonssen notes that Turnbull's pivotal role in the Scottish Enlightenment has come to be recognized in much recent work." "In order to construct a comprehensive educational program, Turnbull drew upon an impressive number of authors, both ancient and modern. Indeed, there is perhaps no better treasure trove of sources for all the various educational debates that took place during the eighteenth century. The work's influence was by no means confined to Scotland. Benjamin Franklin drew generouly upon the Observations in creating his own plan of education in Philadelphia."--Jacket